Inovasi Layanan Pengaduan Online “Lapor Padang” Dalam Meningkatkan Akuntabilitas Pemerintah Kota Padang - Nabila Laila Rani; Miftahul Hasanah; Rifha Tri Oktary; Zara Handayani; Yulia Hanoselina; Yuliarti . (CV. ITTC INDONESIA, 2026)
Public service issues are still characterized by a suboptimal public complaints system, service transparency, and government response to public reports. This study aims to analyze the innovation of the complaint service